Developing pupils’ creativity through 3D modeling: an experimental study - Sosna, Tomáš; Vochozka, Vladimír; Šerý, Michal; Blažek, Josef (Frontiers in Education, 2025)
The research investigates the impact of 3D modeling on the development of creativity in elementary school pupils. The investigation was conducted on a sample of 160 pupils from 5 elementary schools in the South Bohemia region, who were divided into control and experimental groups. The experimental group received technical education lessons using 3D modeling, while the control group worked with traditional methods such as construction kits and physical models. Creativity was assessed using the Torrance Tests of Creative Thinking, which measures four key components of divergent thinking: fluency, flexibility, originality, and elaboration. Statistical analysis showed that 3D modeling had a positive effect on all of these components in the experimental group. On the other hand, there were no statistically significant differences between the experimental and control groups in the output creativity tests results, suggesting that traditional methods can also promote creative thinking. Additionally, there were no significant differences between younger and older students. Based on these findings, we recommend the integration of 3D modeling into the teaching of technical and creative subjects as an effective tool for the development of creativity. Furthermore, it is recommended to combine 3D modeling with other innovative methods and to provide sufficient time for the acquisition of these tools. Future research should focus on the long-term impact of 3D modeling and its integration with augmented and virtual reality to support students’ creative thinking.